2016
DOI: 10.1002/jcph.699
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Tolerability of Metformin in Healthy Elderly Subjects

Abstract: Age-related physiological changes are known to alter the pharmacokinetics (PK) and pharmacodynamics (PD) of drugs. Metformin is commonly used as first-line medication for management of diabetes in elderly patients. However, the PK and PD of metformin have not been sufficiently studied in elderly subjects. Here, 12 elderly subjects, aged 65 to 85 years, and 20 younger healthy volunteers were orally administered 750 mg of metformin 2 hours after dinner, followed by administration of a second dose (500 mg) 12 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Beyond some gastrointestinal symptoms, its most serious side effect, lactic acidosis, is observed only when GFR is below 30 ml/min [ 20 ], far below the cut-off value accepted for a patient to enter the ongoing trials (eGFR> 60 ml/min). This profile will be hopefully maintained also in non-diabetic patients and the fearsome risk of hypoglycemia should remain negligible: clinical trials using metformin in diabetes prevention, in fact, have shown no case of hypoglycemia occurring as serious adverse effect during nearly 18.000 subjects/year of follow-up [ 21 ], nor hypoglycemia is described in obese non-diabetic children assuming the drug [ 22 ], nor in normal subjects after an acute load of metformin [ 23 ]. Such tolerability is a crucial point in a long lasting treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond some gastrointestinal symptoms, its most serious side effect, lactic acidosis, is observed only when GFR is below 30 ml/min [ 20 ], far below the cut-off value accepted for a patient to enter the ongoing trials (eGFR> 60 ml/min). This profile will be hopefully maintained also in non-diabetic patients and the fearsome risk of hypoglycemia should remain negligible: clinical trials using metformin in diabetes prevention, in fact, have shown no case of hypoglycemia occurring as serious adverse effect during nearly 18.000 subjects/year of follow-up [ 21 ], nor hypoglycemia is described in obese non-diabetic children assuming the drug [ 22 ], nor in normal subjects after an acute load of metformin [ 23 ]. Such tolerability is a crucial point in a long lasting treatment.…”
Section: Discussionmentioning
confidence: 99%
“…During expansion, cells were exposed (or not) to 25 μmol/L metformin (Merck, Sigma Aldrich, St. Quentin Fallavier, France). The metformin concentration chosen in our study is close to Cmax observed in ederly subjects, which exhibited higher average Cmax than younger subjects (Jang, Chung et al 2016). At a late passage (P11), cells were exposed (or not) to 0.1 μmol/L compound C (Merck, Sigma Aldrich).…”
Section: Methodsmentioning
confidence: 70%
“…A report showed that gender and race (Caucasians, Blacks, and Hispanics) little affected AUC of metformin [ 120 ]. The elderly subjects (68 ± 2 years) were reported to exhibit 1.7 and 2.0 times higher average C max and AUC than the younger subjects (23 ± 3 years) [ 93 ]. Subjects used in the prediction were young and healthy, excluding effects of both ages and disease on metformin disposition.…”
Section: Resultsmentioning
confidence: 99%